2015
DOI: 10.1007/s12186-015-9140-5
|View full text |Cite
|
Sign up to set email alerts
|

Learn to Lead: Mapping Workplace Learning of School Leaders

Abstract: In recent years policy makers' interest in the professional development of school leaders has grown considerably. Although we know some aspect of formal educational programs for school leaders, little is known about school leaders' incidental and non-formal learning in the workplace. This study aims to grasp what workplace learning activities school leaders value most, what work-related questions incite them to learn, what outcomes they achieve through workplace learning and what conditions support workplace l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
43
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(44 citation statements)
references
References 33 publications
0
43
0
1
Order By: Relevance
“…In light of the job demands–control model (Karasek & Theorell, 1990), one could argue that a high task load causes the demands to outweigh the perceived control, and thus, obstructs the school leader from engaging in more transformational types of learning (Paavola et al, 2004). Indeed, research demonstrated that school leaders in Dutch secondary education face barriers when engaging in professional development, such as a lack of money, time, and resources to initiate change, and to shape their professional future (Hulsbos et al, 2016; Inspectorate of Education, 2014). Thus, in future research, an indicator of work load or pressure would be able to provide insight in whether demands indeed exceed control in school leaders’ current task description, and whether they should be given more time and space to critically reflect on the current status quo and to develop a vision on future development.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In light of the job demands–control model (Karasek & Theorell, 1990), one could argue that a high task load causes the demands to outweigh the perceived control, and thus, obstructs the school leader from engaging in more transformational types of learning (Paavola et al, 2004). Indeed, research demonstrated that school leaders in Dutch secondary education face barriers when engaging in professional development, such as a lack of money, time, and resources to initiate change, and to shape their professional future (Hulsbos et al, 2016; Inspectorate of Education, 2014). Thus, in future research, an indicator of work load or pressure would be able to provide insight in whether demands indeed exceed control in school leaders’ current task description, and whether they should be given more time and space to critically reflect on the current status quo and to develop a vision on future development.…”
Section: Discussionmentioning
confidence: 99%
“…In our view, our approach to school leaders’ professional learning activities enriches our current understanding of how school leaders learn and the factors that facilitate such learning. We hope that the two (social vs. individual) by two (current vs. future) grid for learning activities offers a springboard for future researchers to integrate and further expand this framework including other professional learning activities used in recent studies such as knowledge sharing (van Woerkom, 2003), networking, communities of practice (Hulsbos et al, 2016) reading professional literature and keeping up to date (Geijsel et al, 2009; Kwakman, 2003). Importantly, when changes are implemented in school leaders’ task descriptions, social support systems, and school climate, it should be considered that different aspects of their professional learning might be triggered or inhibited (i.e., social, individual, future- or present-oriented).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…If the history of the concept of leadership is observed [10], we can see how directive leadership (the leader is identified as a school manager), instructional leadership (focused on improving teaching practices), participatory leadership (aimed at participation in decision-making as a key to achieving school progress [11]), transformational leadership (incorporating the existence of a collective vision and the concept of participation) and other similar modalities have emerged, such as postmodern leadership, interpersonal leadership or contingent leadership. Under this umbrella of typologies emerges distributed leadership [12] that considers leadership as an organizational quality in relation to different leadership practices at different levels, although it prioritizes horizontal organizational modalities.…”
Section: Introductionmentioning
confidence: 99%
“…Leaders motivate teachers to work effectively; they do so by creating friendly educational environment for their teams (Spillane, 2004). However, leaders are involved in many processes different in terms of: time load, emotions involved or legal liability (Hulsbos et al, 2015). It is worth to point out that in the Visegrad Group countries and their neighbouring states these leaders are mostly professionally active teachers who are aware of methodical and organisational conditions.…”
Section: Introductionmentioning
confidence: 99%